PROMOTING EUROPEAN INTEGRATION: SECURING EUROPEAN IDENTITY POST COLD WAR - Hendra Manurung (President University, 2016)
On November 13, 2015 a handful of terrorists unleashed a barrage of coordinated attacks at public gathering spots in Paris, France, followed by Belgium twin bombings on 22 March 2016. As the casualty figures climbed and investigators swung into action, news reports were filled with grim comparisons. Some calling it the worst night of violence in France since World War II (1939-1945), and others saying it could be Europe’s most horrific terrorist attack in history. Cutting past any hysteria or hyperbole, it is clear that the Nov. 13 and March 22 attacks have brought to a head the conversation on a number of difficult, overlapping questions facing both Europe and the Middle East. It raised critical European identity. The writer attempt to examine European integration impacts on its identity in descriptive analytical research, and founded that, it might be triggered 4 (four) main strategic issues surrounding the European decision makers, including: First, how might European states shift their stance toward the influx of migrants and refugees coming from war zones in1 Hendra Manurung is a permanent lecturer as well as a head of International Relations Study Program. Corresponding author: h_manurung200273@yahoo.comthe Middle East?; Second, are the capabilities of the Islamic State truly expanding, as recent claims suggest? What are its actual strengths and weaknesses?; Third, what options did Paris and Brussels have in responding to the attacks ? As France steps up the tempo of airstrikes in Syria, will the Vienna talks on Syria’s conflict be radically reshaped?; Fourth, what does the future hold for the Schengen Agreement, and would its unraveling lead the European Union itself closer to dissolution? However, still attractive for those scholars who want to elaborate the European integration progress, as how to predict what’s likely to happen next.